URODYNAMIC FINDINGS IN FEMALE PATIENTS REPORTING WITH LOWER URINARY TRACT SYMPTOMS - Hameed, Nazli; Ali, M Asghar; Azim, Waqar (Journal of Ayub Medical College Abbottabad, 2009)
Objective: The study has been undertaken to determine the reproducibility of lower urinary tract symptoms in female patients after urodynamic investigations. Design: A Descriptive study with retrospective analysis of data. Setting: Combined Military Hospital Rawalpindi and Armed Forces Institute of Urology, Rawalpindi. Methods: Fifty consecutive women with a primary history of urinary incontinence were interviewed on a standard urinary incontinence questionnaire. They underwent structured clinical pelvic examination, along with cough stress test. Post void residual urine was measured. This was followed by a urine routine examination to exclude any urinary infection. Later these patients underwent a combination of urodynamic tests to predict their final diagnosis. The tests performed were filling cystometry and leak point pressures. Results: The clinical diagnosis was found to have a variable reproducibility on urodynamic investigations. Clinical stress incontinence translated as genuine stress incontinence in 61.5% of the cases. Patients with isolated symptoms of stress incontinence had an incidence of detrusor instability up to 33.3%. For the symptoms of urgency and urge incontinence, the diagnosis was reproducible in up to 50% of the cases. In cases of mixed symptoms, 20% patients were found to have stress incontinence and 33.3% cases were found to have an unstable bladder, whereas in 46.6% of the cases no objective abnormality was found on urodynamic investigations. Conclusion: Urodynamic investigations should be performed in female patients with lower urinary tract symptoms, especially if irreversible procedure, e.g., surgery is being contemplated. Keywords: Urinary incontinence, stress incontinence, cystometry, leak point pressure, urinary tract